MALE AND FEMALE EFL JUNIOR HIGH SCHOOL STUDENTS’ PERCEPTION ON THE USE OF MIND MAPPING METHOD TO INCREASE SPEAKING ABILITY - Ifham Muhammad Fauzi (Journal of English Education Program (JEEP), 2021)
This study investigated perception of male and female junior high school students’ on mind mapping method employing qualitative method. Classroom observation was used to get perception of male and female students before conducting the questionnaire. Interview was administered to 2 male and 2 female students from 20 students. The findings revealed that: 1) the male and female students perceived mind mapping method interesting to increase speaking ability; 2) female students were more active and enthusiastic in learning process to increase speaking ability than male; 3) female students submitted a better results of the assignments given by their teacher in effort to increase speaking ability by using mind mapping method; 4) mapping method is very helpful to increase speaking ability of male and female junior high school. This study suggests that the teacher should master and have a better understanding of mind mapping method with the purpose of equipping students various knowledge and English interest to increase their speaking ability. Keywords: gender, mind mapping, perception, speaking ability,